The analysis of traditional fishers’ welfare based livelihood sustainability approach (Case study: Kedung Cowek Surabaya fishers’ community) - Sawiji, Asri; Buchori, Imam; Wahyudi, Noor (UIN Sunan Ampel Surabaya, 2022)
The city of Surabaya has a fairly high Human Development Index, but inequality still exists for marginalized communities such as fishermen on the north and east coasts of Surabaya. Indonesian Traditional Fishermen have an important role in the macro economy and national food security. Traditional Fishers are still included in a marginalized group of people who are very vulnerable to natural and political factors. Efforts to increase the resilience of fishermen need to be carried out by maximizing the assets/capital in the community. The purpose of this study was to assess the livelihood achievement index of fishermen on the dimensions of financial, natural, social and human capital with a case study conducted at the Fishers’ Cooperative Bahari 64 community. Using a quantitative descriptive method, this study conducted a survey of 98 respondents from 130 members who work as a fisherman. From the data analysis it was found that the fishing community of Koperasi Bahari 64 was categorized at a good level with a livelihood index value of 62.26 with an achievement dimension of 62%.